3-D reflection seismic imaging of the Hontomín structure in the Basque-Cantabrian Basin (Spain) - Alcalde, J.; Martí, D.; Juhlin, Christopher; Malehmir, A.; Sopher, D.; Saura, E.; Marzán, I.; Ayarza, P.; Calahorrano, A.; Pérez-Estaún, A.; Carbonell, R. (2013)
The Basque–Cantabrian Basin of the northern Iberia Peninsula constitutes a unique example of a major deformation system, featuring a dome structure developed by extensional tectonics followed by compressional reactivation. The occurrence of natural resources in the area and the possibility of establishing a geological storage site for carbon dioxide motivated the acquisition of a 3-D seismic reflection survey in 2010, centered on the Jurassic Hontomín dome. The objectives of this survey were to obtain a geological model of the overall structure and to establish a baseline model for a possible geological CO2 storage site. The 36 km2 survey included approximately 5000 mixed (Vibroseis and explosives) source points recorded with a 25 m inline source and receiver spacing. The target reservoir is a saline aquifer, at approximately 1450 m depth, encased and sealed by carbonate formations. Acquisition and processing parameters were influenced by the rough topography and relatively complex geology. A strong near-surface velocity inversion is evident in the data, affecting the quality of the data. The resulting 3-D image provides constraints on the key features of the geologic model. The Hontomín structure is interpreted to consist of an approximately 107 m2 large elongated dome with two major (W–E and NW–SE) striking faults bounding it. Preliminary capacity estimates indicate that about 1.2 Gt of CO2 can be stored in the target reservoir.